2022
DOI: 10.5812/aapm.119354
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Relationship Between Depression and Pain Anxiety with Pain Catastrophizing in Patients with COVID-19

Abstract: Background: This study aimed to investigate the relationship between depression and pain anxiety with pain catastrophizing in patients with coronavirus disease 2019 (COVID-19). Methods: In this descriptive, correlational study, 180 patients with COVID-19 in Akhtar and Imam Hossein hospitals in Tehran, Iran, were included from March 2019 to April 2020. All participants completed three questionnaires, including the Pain Catastrophizing Scale (PCS), Pain Anxiety Symptoms Scale (PASS), and Beck’s Depression Invent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Therefore, there is sufficient evidence to support this assumption. The results of this study are almost consistent with the studies of Raiisi et al [18] , Ghasemi et al [19] , and Fisher et al [20] . In explaining this finding, we can say that mental and cognitive factors always play a role in perceiving pain.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, there is sufficient evidence to support this assumption. The results of this study are almost consistent with the studies of Raiisi et al [18] , Ghasemi et al [19] , and Fisher et al [20] . In explaining this finding, we can say that mental and cognitive factors always play a role in perceiving pain.…”
Section: Discussionsupporting
confidence: 93%
“…For example, a study showed, that anxiety about pain and its symptoms are related to psychological constructs such as pain perception and mental pain [18] . Another study indicated the correlation between pain anxiety and pain catastrophizing in patients with COVID-19 [19] . A systematic review showed; significant positive correlations with pain anxiety, pain catastrophizing subscales, and fear of pain in children and adolescents with chronic pain [20] .…”
Section: Introductionmentioning
confidence: 99%
“…Harassment of pain clinic staff is problematic partly due to the opioid misuse crisis (8,9,11), which has been further complicated by the recent pandemic (9,10,18). Socioeconomic challenges, racism, or societal issues may also contribute to the problem of healthcare staff harassment (16,19,20).…”
Section: Discussionmentioning
confidence: 99%